Sistema de plataformas de força e identificação de movimentos por processamento de imagem para aplicação em treinamento do equilíbrio baseado em biofeedback - Lavarda, Marcos Dinís (2016)
The cases of disorders related to upper and lower limbs control directly affect the population. These problems may have its origin due to interruption of sensorimotor communication between the brain and the muscle groups. These factors may be related to aging, neurodegenerative diseases or stroke. Thus, due to the gradual aging of the population, the increase in life expectancy and hence the demand for rehabilitation treatments, several studies in the literature are using biofeedback to rehabilitation of muscle control. However, there is no unified tool that allows the development of exercise protocols for several diseases in a single platform. The aim of this work is to present the development of a visual biofeedback tool, based on force platforms for lower limbs and image acquisition for upper limbs. This system has two interfaces: the first, programmable in high-level, is intended for health professionals to prepare the motor training as needed by the patient; the second is the serious game interface, with which the patient interacts performing the series of activities planned in an exercise games (exergames). The purpose of this study is to provide a programmable rehabilitation platform according to the specific needs of each patient, keeping motivational and interactive features that provide fun activities to reduce evasion of treatments, which are usually carried out for long periods. Moreover, this study shows some tests, approved by the Ethics Committee, with volunteers, applying an exercise protocol to a group of healthy young and comparing the results with a group of elderly volunteers. The results of this study are obtained from two experimental setups: the first is internal to the session in real time, and concerns the scores of volunteers in the game; the second is external to the session, uses the data stored over a stabilometry and compare posturographic data between control and study group. Furthermore, in order to complement the assessments of the developed system, the posturographic data is compared to those obtainded from a commercial baropodometer. Results show that the system is able to perform the estimative of the stabilometry and serious game activities.